Agricultural statistics again - Sagnier, Henry, 1845-1925.
English translation, entitled Agricultural Statistics Again, of an article by Sagnier that appeared in Journal de l'agriculture (1903 January 24).
French agriculturist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Agriculture -- Statistics -- France; Agriculturists -- France